2020
DOI: 10.1111/ipd.12610
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries in preschool children born preterm and/or with low birth weight: A systematic review with meta‐analysis of prevalence data

Abstract: The aim of the present systematic review and meta‐analysis was to evaluate the prevalence of dental caries among preschool children who had been born preterm and/or with low birth weight (LBW) compared with those who had been born full term and/or with normal birth weight (NBW). Eight electronic databases were searched from interception up to November 2018 with no restrictions imposed regarding the date of publication or language. Two independent reviewers screened studies, extracted data, and assessed the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 31 publications
(46 reference statements)
3
29
1
Order By: Relevance
“…Both preterm birth and early childhood caries have common covariables affecting the prevalence, such as socio-economic factors, parental education and smoking. 9 In addition, early childhood caries have a complex aetiology, that is affected by a number of behavioural, dietary and nursing factors, in addition to biology and genetics. 1 Some of the included studies used a blend of confounding factors to adjust the multivariate analyses concerning caries background variables, but we decided to only extract the crude data in order to be able to pool the outcome.…”
Section: Ta B L E 1 Characteristics Of the Included Studies On Pretermentioning
confidence: 99%
See 3 more Smart Citations
“…Both preterm birth and early childhood caries have common covariables affecting the prevalence, such as socio-economic factors, parental education and smoking. 9 In addition, early childhood caries have a complex aetiology, that is affected by a number of behavioural, dietary and nursing factors, in addition to biology and genetics. 1 Some of the included studies used a blend of confounding factors to adjust the multivariate analyses concerning caries background variables, but we decided to only extract the crude data in order to be able to pool the outcome.…”
Section: Ta B L E 1 Characteristics Of the Included Studies On Pretermentioning
confidence: 99%
“…9 The authors concluded that children born preterm had a similar caries experience to those born full term, but the certainty of evidence was very low due to methodological shortcomings. 9 Although children with preterm birth and children with low birthweight were analysed separately, the preterm group included extremely preterm and very preterm children that commonly exhibit intrauterine growth restriction and elevated morbidity rates. 5 One strategy to overcome this overlap is to focus on investigations that have selectively been performed on moderate to late preterm children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most of the published findings support the association between preterm birth and an increase in caries risk, some studies have failed to record statistically significant differences [57,89,90]. Furthermore, a recent systematic review and meta-analysis did not find differences in the prevalence of caries between preschool children born preterm versus full term (91).…”
Section: Caries Riskmentioning
confidence: 99%